A randomized, double-blinded, controlled trial of the effects of fluid rate and/or presence of dextrose in intravenous fluids on the labor course of nulliparas - Fong, Alex; Serra, Allison E.; Caballero, Deysi; Garite, Thomas J.; Shrivastava, Vineet K. (American journal of obstetrics and gynecology, 2017)
Prolonged labor has been demonstrated to increase adverse maternal and neonatal outcome. A practice that may decrease the risk of prolonged labor is the modification of fluid intake during labor. Several studies demonstrated that increased hydration in labor as well as addition of dextrose-containing fluids may be associated with a decrease in length of labor. The purpose of our study was to characterize whether high-dose intravenous fluids, standard-dose fluids with dextrose, or high-dose fluids with dextrose show a difference in the duration of labor in nulliparas. Nulliparous subjects with singletons who presented in active labor were randomized to 1 of 3 groups of intravenous fluids: 250 mL/h of normal saline, 125 mL/h of 5% dextrose in normal saline, or 250 mL/h of 2.5% dextrose in normal saline. The primary outcome was total length of labor from initiation of intravenous fluid in vaginally delivered subjects. Secondary outcomes included cesarean delivery rate and length of second stage of labor, among other maternal and neonatal outcomes. In all, 274 subjects who met inclusion criteria were enrolled. There were no differences in baseline characteristics among the 3 groups. There was no difference in the primary outcome of total length of labor in vaginally delivered subjects among the 3 groups. First stage of labor duration, second stage of labor duration, and cesarean delivery rates were also equivalent. There were no differences identified in other secondary outcomes including clinical chorioamnionitis, postpartum hemorrhage, blood loss, Apgar scores, or neonatal intensive care admission. There is no difference in length of labor or delivery outcomes when comparing high-dose intravenous fluids, addition of dextrose, or use of high-dose intravenous fluids with dextrose in nulliparous women who present in active labor.